Cognitive Modeling in the Management of Economic Growth of the Agriculture in Russia - ANOKHINA, Marina Y.; GOLUBEV, Alexey V.; KONDRASHINA, Olga N. (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019DO - 10.14505//jemt.v10.1(33).12, 2019)
The article analyzes the processes of economic growth in the agriculture in Russia. The current state of the agriculture, characterized by a variety of technological structures and various levels of economic and social development of enterprises and rural areas, has been considered. Tendencies of development and the reasons restraining the further growth of industry have been shown. The parametric content of management system of economic growth of agriculture has been determined on the basis of cognitive modeling. A fuzzy cognitive map for management of economic growth of the industrial complex has been developed, the static and dynamic analysis of which allowed obtaining forecasts of the dynamics of agriculture under various management influences. As a result, a strategy for achievement of the target parameters of the economic dynamics of the agricultural economy has been formed. A conclusion on the prospects for the development of the agriculture with an effective agrarian policy is drawn.